Cellulose nanofiber board. (1st May 2018) - Yousefi, Hossein; Azad, Sona; Mashkour, Mahdi; Khazaeian, Abolghasem
Highlights: Cellulose nanofiber board (CNF-board) with high mechanical properties was fabricated. No chemical additives or adhesives were used to make CNF-board. A novel pre-press apparatus was made to dewater highly absorbent CNF gel. CNF-board showed self-densification and dimensional recovery capabilities. Flexural test of CNF-board was carried out thanks to the high thickness of CNF-board. Abstract: A cellulose nanofiber board (CNF-board) with a nominal thickness of 3 mm was fabricated without adhesive or additive. To provide comparison, a cellulose fiber board (CF-board) was also fabricated. A novel cold pre-press apparatus was made to dewater highly absorbent CNF gel prior to drying. A mild drying condition in the vacuum oven at 70 °C and 0.005 MPa was enough to provide the CNF-board with a density of 1.3 g/cm 3 thanks to its self-densification capability. Unlike the CF-board, the fabricated CNF-board had a high water-activated dimensional recovery ratio (averagely 96%) during the five cyclic wetting-drying process. The flexural and tensile strengths of CNF-board obtained were 162 MPa and 85 MPa, respectively. The corresponding values for CF-board were 28 MPa and 11 MPa, respectively. The specific flexural and tensile strengths of CNF-board obtained were higher than those of CF-board as well as some other traditional wood-based composites, polymers and structural ASTM A36 steel.